THE PHENOMENON OF ONLINE GAMBLING AMONG STUDENTS - Azka Wibowo; Melvin; Zharif; Rizky; Marvel; Sri Anawati (Journal of International Islamic Law, Human Right and Public Policy, 2025)
The rapid development of technology and the internet has brought numerous conveniences to everyday life but has also triggered new social issues, one of which is the rise of online gambling. This activity now extends beyond adults and increasingly involves students. This study employs a qualitative research design using a literature review approach, analyzing both national and international sources published between 2013 and 2023. Data are interpreted through Max Weber’s theory of social action and a phenomenological framework to understand students’ behaviors and motivations in engaging with online gambling. The findings indicate that online gambling among students leads to severe consequences across social, economic, psychological, and academic domains. Addicted adolescents often experience family conflict, financial loss, poor academic performance, and sometimes criminal involvement. The ease of internet access is a primary factor facilitating this behavior, exacerbated by weak supervision from families and communities. Many students are initially drawn by the thrill of easy profits, which soon traps them in a cycle of addiction.